2007
DOI: 10.1620/tjem.213.113
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Stem Cell Infusion in Heart Transplant Candidates

Abstract: The stem cell transplantation is emerging as a potential therapeutic modality for patients with heart failure. It has been demonstrated that intracoronary stem cell transplantation had beneficial effects on left ventricular perfusion and contractile functions. We hypothesized that patients with end-stage ischemic cardiomyopathy, who are candidates for heart transplantation, could also benefit from autologous intracoronary stem cell transplantation. We performed a prospective, openlabeled study in 10 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Human skeletal stem cells (also known as human bone marrow-derived stromal cells (hBMSC)) are adult multipotent stem cells located in the bone marrow perivascular niche and are recruited to bone formation sites during bone remodeling [ 1 ]. During recent years, hBMSC have been tested in a number of clinical trials for their ability to enhance tissue repair including tissue regeneration where hBMSC were injected locally at the sites of tissue injury; for example, bone fracture [ 2 4 ] or ischemic myocardium [ 5 8 ]. However, systemic intravenous infusion is more suitable for clinical cell transplantation and is employed for hematopoietic stem cell (HSC) transplantation with success and where HSCs, following homing from systemic circulation to bone marrow, engraft and initiate hematopoiesis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human skeletal stem cells (also known as human bone marrow-derived stromal cells (hBMSC)) are adult multipotent stem cells located in the bone marrow perivascular niche and are recruited to bone formation sites during bone remodeling [ 1 ]. During recent years, hBMSC have been tested in a number of clinical trials for their ability to enhance tissue repair including tissue regeneration where hBMSC were injected locally at the sites of tissue injury; for example, bone fracture [ 2 4 ] or ischemic myocardium [ 5 8 ]. However, systemic intravenous infusion is more suitable for clinical cell transplantation and is employed for hematopoietic stem cell (HSC) transplantation with success and where HSCs, following homing from systemic circulation to bone marrow, engraft and initiate hematopoiesis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…No adverse events related to the procedure were found, and no arrhythmias were reported. Therefore, this group also concluded that the procedure is safe [ 44 ]. • The only randomized controlled study of cell-based therapy in HF patients to date is the TOPCARE-CHD (Transplantation of Progenitor Cells and Recovery of Left Ventricular Function in Patients With Nonischemic Dilatative Cardiomyopathy) trial of 75 patients with a history of MI at least 3 months before the start of the study and regional left ventricular dysfunction.…”
Section: Lessons Learned From Clinical Trialsmentioning
confidence: 99%